Cross-border mergers and greenfield foreign direct investment - Ignat Stepanok (Stockholm School of Economics, The Economic Research Institute (EFI), 2010)
I present a model of international trade and foreign direct investment (FDI), where FDI is comprised of greenfield FDI and mergers and acquisitions (M&A). Working in a monopolistically competitive environment, merging firms do not reduce competition. Mergers are motivated by efficiency gains and transfer of technology and expertise. Following empirical evidence, I model greenfield investors as the more productive group relative to M&A firms. The model has two symmetric countries and generates two-way flows of both M&A and greenfield FDI. Greater proximity to a market makes more firms choose greenfield FDI over M&A when investing there. Empirical evidence supports this result.
Keywords: F12; F23; O41; 330; Foreign direct investment; Mergers; Greenfield; Firm heterogeneity; Direktinvestition; Übernahme; Internationale Markteintrittsstrategie; Multinationales Unternehmen; Monopolistischer Wettbewerb; Theorie